2015
DOI: 10.1073/pnas.1500804112
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal control of locomotor handedness in Drosophila

Abstract: Genetically identical individuals display variability in their physiology, morphology, and behaviors, even when reared in essentially identical environments, but there is little mechanistic understanding of the basis of such variation. Here, we investigated whether Drosophila melanogaster displays individual-toindividual variation in locomotor behaviors. We developed a new high-throughout platform capable of measuring the exploratory behavior of hundreds of individual flies simultaneously. With this approach, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
187
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(209 citation statements)
references
References 52 publications
(52 reference statements)
22
187
0
Order By: Relevance
“…The pairwise transition rates between clusters appeared to be idiosyncratic as well. These findings are consistent with behavioral individuality in Drosophila phototaxis (Kain et al 2012), locomotor handedness (Buchanan et al 2015) and thermal preference . However, the clear evidence of individuality in PCA 20 -GMM-SW cluster abundance distributions is notable when compared to the lack of signal of such individuality in the supervised classification results of Kain et al (2013).…”
Section: Discussionsupporting
confidence: 85%
“…The pairwise transition rates between clusters appeared to be idiosyncratic as well. These findings are consistent with behavioral individuality in Drosophila phototaxis (Kain et al 2012), locomotor handedness (Buchanan et al 2015) and thermal preference . However, the clear evidence of individuality in PCA 20 -GMM-SW cluster abundance distributions is notable when compared to the lack of signal of such individuality in the supervised classification results of Kain et al (2013).…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, we did not find that our thermogenetic manipulations substantially reduced activity level with the exception of one (activation of P-F-Rs through SS02293-Gal4). As seen previously (Akhund-Zade et al, 2019;Ayroles et al, 2015;Buchanan et al, 2015), the mean turn bias in all experimental groups was approximately 0.5 (0.49 +/-0.011). The variability in turn bias ranged from 0.09 to 0.15 (standard deviation) across all experimental groups ( Fig S2B).…”
Section: Neural Circuit Elements Mediating Ldmsupporting
confidence: 85%
“…To examine how sensory context (specifically, changes in luminance) affects individual locomotor biases, we modified instruments previously used to track flies as they made left-right locomotor choices in symmetrical Y-shaped mazes (Ayroles et al, 2015;Buchanan et al, 2015). We added a dual-channel illuminator, under computer control, so that behavioral arenas could be lit with white LEDs, infrared LEDs, or both ( Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, upon AA challenges, we observed that some flies increased their total time on yeast by having many short yeast visits, while some flies had fewer but longer visits. It will be interesting to investigate if these differences reflect behavioral idiosyncrasies, as observed before in many animals including Drosophila (Buchanan and de Bivort, 2015; Dingemanse et al, 2010; Kain and de Bivort, 2012). Differentiating between these two possibilities and identifying the physiological and circuit mechanisms leading to idiosyncrasies will be key to a better understanding of behavior.…”
Section: Discussionmentioning
confidence: 85%